2017
DOI: 10.1111/apt.14436
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: thiopurines decrease the risk of colorectal neoplasia in patients with inflammatory bowel disease

Abstract: This meta-analysis revealed an antineoplastic effect of thiopurines on colorectal neoplasia in patients with IBD, particularly amongst patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 56 publications
(219 reference statements)
0
40
0
Order By: Relevance
“…Thiopurines are immunosuppressants that exert corticosteroid‐sparing efficacy, and can retain remission and prevent relapse in a considerable proportion of patients with IBD. In our meta‐analysis, we assessed the effect of thiopurines on the risk of developing colorectal neoplasia, and demonstrated thiopurines had an antineoplastic effect on high‐grade dysplasia and colorectal cancer, particularly in ulcerative colitis (UC) . Some of these findings were different from those presented in the latest meta‐analysis by Jess et al in 2014, and we had discussed the differences between our study and Jess's in our meta‐analysis …”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Thiopurines are immunosuppressants that exert corticosteroid‐sparing efficacy, and can retain remission and prevent relapse in a considerable proportion of patients with IBD. In our meta‐analysis, we assessed the effect of thiopurines on the risk of developing colorectal neoplasia, and demonstrated thiopurines had an antineoplastic effect on high‐grade dysplasia and colorectal cancer, particularly in ulcerative colitis (UC) . Some of these findings were different from those presented in the latest meta‐analysis by Jess et al in 2014, and we had discussed the differences between our study and Jess's in our meta‐analysis …”
mentioning
confidence: 53%
“…We thank Drs Laharie and Riviere for their interest in our work . As they mentioned, IBD is characterised by chronic recurrent intestinal inflammation, usually associated with increased risk of malignancies, especially gastro‐intestinal carcinomas.…”
mentioning
confidence: 92%
“…Recent work suggests that it is cumulative inflammatory burden which contributes to development of CRC, thus in theory any drug preventing inflammation might mediate this risk . Whether there are specific chemopreventive benefits for aminosalicylates is unclear . It has been hypothesised that aminosalicylates may specifically reduce colorectal dysplasia risk secondary to activation of peroxisome proliferator‐activated receptor‐γ, free radical scavenging, or inhibition of the Wnt/β‐catenin pathway .…”
Section: Discussionmentioning
confidence: 99%
“…66 Whether there are specific chemopreventive benefits for aminosalicylates is unclear. 67 It has been hypothesised that aminosalicylates may specifically reduce colorectal dysplasia risk secondary to activation of peroxisome proliferator-activated receptor-γ, 68 free radical scavenging, 69 or inhibition of the Wnt/β-catenin pathway. 70 Nevertheless, the low absolute risk of developing CRC in UC is unlikely to make use of aminosalicylates for chemoprevention a cost effective strategy, thus they are not recommended solely for cancer prevention in patients with UC.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…In the present updated meta-analysis including results from six additional studies and pooling data from 24 cohort, case-control and population-based studies, Lu et al observed an antineoplastic effect of thiopurine on high-grade dysplasia and colorectal cancer, especially in ulcerative colitis (UC). 8 In daily practice, despite the increase in IBD therapeutic armamentarium and safety signals on thiopurines, these conventional immunosuppressants remain often used. According to French national health insurance data collected from 2009 to 2013 among 210,001 patients, the 1-year cumulative probabilities for receiving thiopurine were 37.1% in CD and 15.2% in UC newly diagnosed.…”
mentioning
confidence: 99%